Association between the concentrations of some toxic metals and the risk of uterine fibroids among Nigerian women - Fatimoh Bukola Kareem; Mathias Abiodun Emokpae (Wolters Kluwer Medknow Publications, 2022)
Background: Uterine fibroids are a major health challenge to some women in the world, especially women of African descendants. The etiology of uterine fibroids and the mechanisms of their growth are not fully understood, and those factors that make women to be susceptible to fibroid development are subjects of investigation. Environmental toxicants such as toxic metals exposure have been implicated, but the results have not been consistent. This study seeks to determine the association between blood cadmium (Cd), arsenic (As), and lead (Pb) levels and the risk of uterine fibroids among women of reproductive age. Materials and Methods: This case-control study comprised 100 women of reproductive age (age range, 20-50 years) with uterine fibroid and 50 age-matched women without uterine fibroids. Fibroids were diagnosed using abdominal scan by attending physicians. Furthermore, the control subjects were screened for fibroids using abnormal scan. Blood Cd, As, and Pb were determined using an atomic absorption spectrophotometer, and the risk of association was calculated. Results: The mean blood Cd, As, and Pb were significantly higher (P < 0.001) among women with fibroid than those without fibroid (controls). The odds ratio for Cd 2.62 (confidence interval [CI]: 0.02-0.05), As 1.02 (CI: 0.02-0.030), and Pb 1.42 (CI: 0.04-0.129) was greater among women with uterine fibroids than controls. Conclusions: Exposure to cadmium and lead might be a risk factor for developing uterine fibroids among Nigerian women.